Redesain Birokrasi sebagai Strategi Pemerintah untuk Meningkatkan Efektivitas Pelayanan Publik - Mujahidin Mujahidin; Fanila Kasmita Kusuma (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study investigates Indonesia’s bureaucratic redesign as a strategic response to enhance public service effectiveness in the post-decentralization and post-pandemic era. Drawing on a qualitative approach and literature-based analysis, the research explores four interrelated dimensions: organizational structure reform, digital transformation (SPBE), adaptive work culture, and post-pandemic governance strategies. Findings indicate that while regulatory frameworks such as PermenPAN-RB No.?28/2019 and SPBE initiatives provide formal direction, their implementation is shaped by institutional capacity, cultural alignment, and leadership commitment. Structural reforms often fall short due to insufficient capacity-building and performance incentives, while digital initiatives reveal spatial inequality and interoperability challenges. The adoption of adaptive cultural values, notably through the BerAKHLAK framework, shows promise but remains uneven. Similarly, hybrid service models introduced during the pandemic highlight Indonesia’s strategic responsiveness, yet their impact varies across regions. The study offers a synthesized analysis combining empirical findings and theoretical insights, emphasizing the need for coherent, context-sensitive reforms that integrate structural, digital, and cultural components. This research contributes to public administration scholarship by reframing bureaucratic transformation as both a technical and political process requiring iterative adaptation, inclusive governance, and long-term institutional learning.